Survey of Workplace Smoking Restrictions Part 1 of 2 (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Tobacco Institute survey of corporate smoking control policies. Highlights "marked increase in and nature of anti-smoking activity in work environment." Reviews legislation, smoking cessation programs, written and unwritten smoking restriction policies, reports from field staff, and other surveys of smoking restrictions.